THE ANALYSIS OF NON-LITERAL MEANING IN CHRISTMAS CAROL BY CHARLES DICKENS - Maria Salvatrix B.B. Nimanuho (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
This study investigates non-literal meaning in ‘Christmas Carol’ story written by a famous British author, Charles Dickens. This study used a descriptive qualitative method. The data were taken or collected from words, phrases, and sentences on ‘Christmas Carol’ novella, without reducing, adding, or changing any parts from the original source. The data were analyzed to answer three research questions: (1) What types of non-literal meaning are found in Christmas Carol story? (2) What are the interpretations of those non-literal meanings found in Christmas Carol story? (3) What is the most dominant type of non-literal meaning found in Christmas Carol story? In order to avoid bias, validator triangulation was used. The study found 11 idiom, 14 Simile, 6 Hyperbole, 6 Alliteration, 5 Personification, 3 Anaphora, 3 Onomatopoeia, 2 Irony, 2 Synecdoche, 2 Sarcasm, 1 Metaphor, and 1 Litotes. Simile was the non-literal meaning’s type which was mostly used in the story, although the percentage was still less than 50%. These findings indirectly could help the readers to understand deeper the message or the story that the author wants to convey. It is suggested for future researchers to investigate the non-literal meaning of others literary works such as tale, folklore, fairy tale, short-story, fable, etc. and media such as movie, drama, speech script etc. It is because other type of non-literal meaning and different ways of using them could be found in these literary works and media. This study will improve our understanding about non-literal meaning. Keywords: Semantics, Non-Literal meaning, Christmas Carol, Novella, Charles Dickens